Relationship Between Mother's Knowledge In Handling Fever Seizures In Infants And Toddlers In Nagari Ampiang Parak Timur, District Sutera, Pesisir Selatan. - Saputra, Nopan (Sahabat Publikasi Kuu, 2025)
Introduction: Fever accompanied by seizures is the most feared event by parents, seizures that are not treated properly will be fatal for babies and toddlers, knowledge of handling febrile seizures is the main factor that mothers must have so that nothing dangerous happens. Therefore, parents must know how to handle children who have seizures, so that the child gets fast and appropriate treatment, especially if the seizures last a long time and are repeated. Methods : This study is a quantitative study with a cross-sectional study design. This study uses a non-parametric statistical test, namely the Gamma Test to measure the relationship between two ordinal scale variables with a sample size of 31 respondents. Results : This study used the Gamma Test with the results obtained pvalue = 0.000 (p < 0.05). Conclusion : It is recommended that further researchers examine factors related to maternal readiness in handling febrile seizures at home.